Struggle in Arthur Kopit’s Indians (Journal of the College of Basic Education, 2022)
This research plans to focus on the struggle in Arthur Kopit’s Indians. Arthur Kopit (1937) is one of the remarkable American playwrights whose work implies his profound anxiety and compassion for humanity. Kopit’s main literary concern is exposing the falsehood of the American history as well as the hypocrisy of the fabricated mythic image of the American hero and America’s continuing insistence to create such myths and legends to rationalize its horrible deeds and racial domination of the less powerful and inferior societies. Kopit’s Indians (1968) is considered as his masterpiece in which he depicts through his characters, America’s harshly unjust treatment of Native Americans in the Nineteenth century and admittedly suggests a hint of America brutal involvement in the Vietnam War, its mass killing of the Vietnamese and the troubled period of the Sixties. Buffalo Bill who is the central character of the play fails to create a friendly relationship between the Whites and the Indians; thus he facilitates the course of the American plan to defeat them and control their land. The research also seeks to prove that U.S. government is satisfied with the act of mass extermination of others, by all means possible for the sake of their own benefits.